Immune complex induced arthritis in rats: role of lipid mediators on cell infiltration - F. A. C. Rocha; L. E. C. Andrade; S. Jancar (Mediators of Inflammation)
We investigated the participation of lipid mediators in an experimental immune complex (IC) arthritis model in rats. The animals were subjected to intraarticular injection of anti-bovine sertLm albumin (BSA) IgG antibodies followed by i.v. injection of BSA. Histopathological analysis of the synovial membranes disclosed infiltration of polymorphonuclear (PMN) cells and vascular congestion. Slight increase in vascular permeability, measured by Evans blue dye extravasation into the joints, was detected after 3 h of arthritis. Cellular influx into the articular cavities was most evident at the sixth hour of arthritis with predominance of PMN. Pretreatment with either indomethacin, a cyclooxygenase inhibitor, or L-660,711, a peptido-leukotriene antagonist, did not inhibit cell infiltration, whereas pretreatment with either L-663,536, a 5-lipoxygenase inhibitor, or L-655,240, a thromboxane antagonist, significantly inhibited the phenomenon. Pretreatment with WEB 2170, a platelet activating factor (PAF) antagonist, also significantly inhibited cell influx. These results suggest that thromboxane, LTB4 and PAF mediate cell infiltration in this IC arthritis model.